Identification Role Of Teacher In Provide Education Reproductive Health ( KRR ) For Adolescent With Disability Blind In SLB Aisyiyah Ponorogo - Inna Sholicha Fitriani (Universitas Muhammadiyah Ponorogo, 2019)
Adolescent with disability blind is part of an individual who require special needs. Changes of reproductive organs and hormone influence it well as the teenager included in sexuality.The case has occur to adoledcents with disability blind is the lack of the provision of education sexual and reproductive health. The purpose of this research to identify role of teacher in provide education reproductive health ( KRR ) for adolescent with disability blind in SLB Aisyiyah Ponorogo. The kind of research this descriptive quantitative, the population it is all of it the teachers in SLB Aisyiyah Ponorogo. The sample this is as many as 12 respondent. Data research were analysed with collection data, reduction data and categorization, verification and presentation of data, draw conclusions. Education program of KRR give to prevent health in early adolescence pertaining to physical health which includes the social system functions and the process of reproduction. The topic is about anatomy and the functioning of an organ reproduction, a sign of puberty, and all about diseaseas of reproduction, as well as education reproduction sex and gender given uses the method a braille book, a puppet reproductive health, and daisy format. The delivery of KRR carried out at the time of the subject matter IPA and PAI, teacher was support in the implementation of education services health KRR for adolescent with disability blind